Diarrhea caused by viruses in transplant recipients. Issue 3 (21st April 2014) - Lee, L.Y.; Ison, M.G.
Abstract Diarrhea is a common complication after solid organ transplantation, and viruses are emerging as important but underestimated causative agents. Viral infections in solid organ transplant (SOT) recipients can result in severe and prolonged diarrhea with significant patient morbidity and graft complications. Cytomegalovirus remains the most common of the viruses to cause diarrhea, but other viruses are being increasingly recognized, including norovirus, rotavirus, and adenovirus. This article reviews the epidemiology, clinical presentation, diagnosis, management, and outcomes of these viral causes of diarrhea in SOT patients.